Answer:
The inverse function f^-1 (x) = (1/5) x
Step-by-step explanation:
* Lets explain what is the meaning of f^-1(x)
- f^-1 (x) the inverse function of f(x)
* How to find the inverse function
- In the function f(x) = ax + b, where a and b are constant
- Lets switch x and y
∵ y = ax + b
∴ x = ay + b
* Now lets solve to find y in terms of x
∵ x = ay + b ⇒ subtract b from the both sides
∴ x - b = ay ⇒ divide the two sides by a
∴ (x - b)/a = y
∴ The inverse function f^-1 (x) = (x - b)/a
* Lets do that with our problem
∵ f(x) = 5x ⇒ y = 5x
∴ x = 5y
- Find y in terms of x
∵ x = 5y ⇒ divide the both sides by 5
∴ x/5 = y
∴ f^-1 (x) = (1/5) x
* The inverse function f^-1 (x) = (1/5) x